KEBIJAKAN HUKUM TERHADAP FENOMENA AI VOICE CLONING DI INDONESIA - Dadang Rachmat; Mustofa Kamil; Ervawati; Dede Agus Sodikin; Djamal Efendi (Berajah Journal, 2026)
The development of Artificial Intelligence (AI) technology has produced significant innovations, including AI Voice Cloning which enables replication of human voice with very high accuracy. Although this phenomenon has potential positive applications in various sectors, it also poses serious risks related to fraud, identity falsification, privacy violations, and intellectual property rights infringement. In Indonesia, specific regulations regarding AI Voice Cloning are not yet available, so handling this phenomenon relies on interpretation from various existing legal instruments. This study analyzes the relevant legal framework, jurisdictional challenges, and socio-economic implications of AI Voice Cloning using normative legal research methods and interdisciplinary approaches. The results show that Indonesian legal policy requires comprehensive development covering technical regulations, protection of voice rights as intellectual property objects, digital verification mechanisms, and harmonization with international standards. This study recommends the formation of specific regulations, strengthening law enforcement capacity, and developing an AI ethics ecosystem involving multi-stakeholders.